Pre- and Postnatal Vitamin D Status and Allergy Outcomes in Early Childhood - Kristina Rueter; Aris Siafarikas; Debra J. Palmer; Susan L. Prescott (Biomedicines, 2022)
The dramatic increase in the prevalence of allergic disease in recent decades reflects environmental and behavioural changes that have altered patterns of early immune development. The very early onset of allergic diseases points to the specific vulnerability of the developing immune system to environmental changes and the development of primary intervention strategies is crucial to address this unparalleled burden. Vitamin D is known to have immunomodulatory functions. While allergic disease is multifactorial, associations with reduced sunlight exposure have led to the hypothesis that suboptimal vitamin D levels during critical early periods may be one possible explanation. Interventions to improve vitamin D status, especially in early life, may be the key to allergic disease prevention.